The Jejuluk in Komering tribe weddings in the globalization from a siyasa perspective - Yusdani,; Ahmad Arifai,; Januariansyah Arfaizar, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
This article discusses jejuluk as the bestowing of traditional titles to the bride and groom in the Komering tradition after the wedding. This tradition is still preserved in the Komering community today. This article looks at the reason why it is important for the Komering people to bestow titles at a wedding ceremony, and how this tradition is maintained. This article is based on a study conducted in Tanjung Lubuk District, Ogan Komering Ilir Regency, South Sumatra. The study used symbol theory that integrated an ethical approach with the meaning of symbols based on the researcher's perspective. This study also used an emic perspective, which is a cultural understanding based on the owner of the culture. Data collection was carried out using three techniques: observation, in-depth interviews, and secondary data. In this research, two levels of analysis were used: interpretive qualitative analysis because this research is cultural research and analysis from the perspective of siyasa. This research shows that jejuluk is a tradition inherited from the ancestors to support the building of a sakinah, mawaddah, and rahmah family because it has the values ​​of harmony and nobility. From the perspective of siyasa, jejuluk can be interpreted as a strategy for the Komering community to preserve local wisdom and values ​​in marriage, so their traditions and cultural roots of their ancestors are not lost amidst the strong currents of globalization.